2020
DOI: 10.1111/ane.13222
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in three cases after brivaracetam treatment during pregnancy

Abstract: Background Use of certain antiseizure drugs (ASDs) during pregnancy increases the risk of major congenital malformations, while less is known about newer ASDs. Based on the safety of levetiracetam, brivaracetam may be similarly safe in pregnancy; however, no cases have been published to date. Aims of the Study We retrospectively identified three women with epilepsy treated with brivaracetam during pregnancy and described the maternal and neonatal outcomes. Methods We reviewed the patients' medical records as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
0
12
0
4
Order By: Relevance
“… 48 50 There is no sign of teratogenicity in rat or rabbit models. 51 Until to date, only three reports of WWE treated with brivaracetam during pregnancy. 51 One woman had idiopathic generalized epilepsy (patient 1) and two had focal epilepsies (patient 2 and patient 3).…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
See 1 more Smart Citation
“… 48 50 There is no sign of teratogenicity in rat or rabbit models. 51 Until to date, only three reports of WWE treated with brivaracetam during pregnancy. 51 One woman had idiopathic generalized epilepsy (patient 1) and two had focal epilepsies (patient 2 and patient 3).…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
“… 51 Until to date, only three reports of WWE treated with brivaracetam during pregnancy. 51 One woman had idiopathic generalized epilepsy (patient 1) and two had focal epilepsies (patient 2 and patient 3). Brivaracetam doses ranged from 50 to 200 mg/day.…”
Section: Management Of Epilepsy During Pregnancy and Anti-seizure Med...mentioning
confidence: 99%
“…In the FDA drug labeling, the evidence provided by animal studies showed that these three ASMs had developmental toxicity in pregnant rats or rabbits at clinically relevant doses or at plasma exposures greater than clinical exposures, including visceral abnormalities, skeletal abnormalities, decreased fetal weight and embryo-fetal death for perampanel exposure at dose of 1, 3 or 10 mg/kg/day, skeletal abnormalities, decreased fetal weight and embryo-fetal death for rufinamide exposure at dose of 20, 100, and 300 mg/kg/day, and embryo-fetal death and decreased fetal weight only for highest dose brivaracetam exposure. One case report reported 2 cases of minor congenital malformations in the offspring exposed to brivaracetam during pregnancy (Paolini et al, 2020). As a result, our model can be used as a tool to alert new drugs that still lack clinical evidence for teratogenicity.…”
Section: Figure 4 |mentioning
confidence: 91%
“…These anomalies included de novo unbalanced chromosomal 18, conjoined twins, congenital knee dislocation, talipes, and cytogenic abnormality with most deemed unlikely related to eslicarbazepine exposure 54 . Lacosamide has three published exposures in pregnancy and no major congenital malformations observed in offspring, 55 whereas brivaracetam has three published exposures (two on polypharmacy) with no observed major congenital malformation, although minor malformations were described, including congenital dermal melanocytosis, ankyloglossia (n = 1), and hemangioma on the thumb and back (n = 1) 56 . The available data on newer antiseizure medications are currently insufficient to draw conclusions.…”
Section: Preconception Counselingmentioning
confidence: 99%